Control Strategy for Three Phase Shunt Active Power Filter with Minimum Current Measurements - Y. Kusuma Latha; Ch. Saibabu; Y.P. Obulesh (Institute of Advanced Engineering and Science, 2011)
The active power filter has been proved to be an effective method to mitigate harmonic currents generated by nonlinear loads as well as to compensate reactive power. The methods of harmonic current detection play a crucial part in the performance of active power filter (APF). This paper presents a new control strategy in which three Shunt Active Power filter Configurations aredeveloped in order to define new simple control algorithm which requires minimum number of current measurements. The effecticeveness of the proposed control strategies are demonstrated through results. The entire control system is implemented with MATLAB/SIMULINK. The simulation results are presented for different control strategies and comparison is made among themDOI:http://dx.doi.org/10.11591/ijece.v1i1.23